Dormia Basket versus Extraction Balloon in Proximally Migrated Biliary Stents - Aya Mohammed Mahros; Asem Ahmed Elfert; Hebatallah Abdel Maksoud; Mahmoud Elkerdawy; Mai Moustafa Fahmy; Mohammed Hussien Ahmed (Journal of the Pakistan Medical Association, 2023)
Objective: To compare balloon extraction versus Dormia basket in the retrieval of proximally migrated stent. Methods: The prospective study was conducted at Tanta University Hospital and Kafrelsheikh University Hospital, Egypt, from December 2019 to December 2020, and comprised adult patients of either gender who presented with proximally migrated biliary plastic stent who were evaluated with respect to risk factor for migration. The difference in efficacy of and Dormia basket group A and balloon extraction group B was evaluated. Data was analysed using SPSS 21. Results: Of the 80 patients, 43(53.8%) were males and 37(46.3%) were females. The overall mean age was 55.7±14.2 years. Group A had 40(50%) patients; 21(52.2%) males and 19(47.5%) females with mean age 56.9±14.1 years. Group B had 40(50%) patients; 22(55%) males and 18(45%) females with mean age 54.6±14.5 years. (p>0.05). Change-over to the other method was done in 15(37.5%) patients of group A and in 8(20%) of group B (p=0.084).Mean time of the procedure was 57.4±21.7min in group A and 37.5±21.6min in group B (p ≤0.001). Complications occurred in 3(7.5%) group A patients and 2(5.0%) group B patients (p=1.0). Conclusion: Balloon extraction was found to be more successful than Dormia basket in the extraction of proximally migrated stent. Keywords: Cholangiopancreatography, Endoscopic retrograde, Cholestasis, Stents, Cholangitis.